EFFECT OF SENSORY –MOTOR INTEGRATIONTECHNIQUES ON IMPROVING THE DEXTERITY OFHAND IN HANSEN’S DISEASE - Patil, Maithili S.; Varadharajulu, G. (International Journal of Psychosocial Rehabilitation, 2020)
The study was done to determine the effects of Sensory –Motor integration techniques on improving the dexterity of hand in Hansen’s disease .In the study , 30 patients were participated who were affected with Hansen’s disease and showing the symptoms of early Neuropathy i.e. decreased sensation of hand and weakness of hand muscles . The patients were first tested with eight dexterity tests to check the power of hand dexterity. Then they were received different Sensory –Motor integration techniques ,5 days in a week up to four weeks .Then again patients were tested with the same dexterity tests .At the end of the study the data was analyzed and compared statistically by using paired t-test.Out of 30 patients 17 were male patients and 13 were female patients with the age group of 40-60 years.The statistical data were shown the comparison of mean values of all dexterity tests, pre and post treatment along with their standard deviation. The values were compared within the group by applying paired t –test. It shown that there is significant improvement in the dexterity of hand in patients affected with Hansen’s disease after giving the Sensory –Motor integration techniques. CONCLUSION-Based on the statistical analysis and interpritations, the Sensory –Motor integration techniques are significantly effective on improving the dexterity of hand in Hansen’s disease.